The Effects of Topic Knowledge on Intelligibility and Lexical Segmentation in Hypokinetic and Ataxic Dysarthria - Utianski, Rene L. (2011)
Benefits to speech intelligibility can be achieved by enhancing a listener’s ability to decipher it. However, much remains to be learned about the variables that influence the effectiveness of various listener-based manipulations. This study examined the benefit of providing listeners with the topic of some phases produced by speakers with either hypokinetic or ataxic dysarthria. Total and topic word accuracy, topic-related substitutions, and lexical boundary errors were calculated from the listener transcripts. Data were compared with those who underwent a familiarization process (reported by Liss, Spitzer, Caviness, & Adler, 2002) and with those inexperienced with disordered speech (reported by Liss Spitzer, Caviness, & Adler, 2000). Results revealed that listeners of ataxic speech provided with topic knowledge obtained higher intelligibility scores than naïve listeners. The magnitude of benefit was similar to the familiarization condition. However, topic word and word substitution analyses revealed different underlying perceptual mechanisms responsible for the observed benefit. No differences attributable to listening condition were discovered in lexical segmentation patterns. Overall, the results support the need for further study of listener-based manipulations to elucidate the mechanisms responsible for the observed perceptual benefits for each dysarthria type.